CCR7 Modulates the Generation of Thymic Regulatory T Cells by Altering the Composition of the Thymic Dendritic Cell Compartment - Zicheng Hu (Cell Reports, 2017)
Upon recognition of auto-antigens, thymocytes are negatively selected or diverted to a regulatory T cell (Treg) fate. CCR7 is required for negative selection of auto-reactive thymocytes in the thymic medulla. Here, we describe an unanticipated contribution of CCR7 to intrathymic Treg generation. Ccr7−/− mice have increased Treg cellularity because of a hematopoietic but non-T cell autonomous CCR7 function. CCR7 expression by thymic dendritic cells (DCs) promotes survival of mature Sirpα− DCs. Thus, CCR7 deficiency results in apoptosis of Sirpα− DCs, which is counterbalanced by expansion of immature Sirpα+ DCs that efficiently induce Treg generation. CCR7 deficiency results in enhanced intrathymic generation of Tregs at the neonatal stage and in lymphopenic adults, when Treg differentiation is critical for establishing self-tolerance. Together, these results reveal a complex function for CCR7 in thymic tolerance induction, where CCR7 not only promotes negative selection but also governs intrathymic Treg generation via non-thymocyte intrinsic mechanisms.